Resource Allocation During the Transition to a Market Economy : Policy Implications of Supply Bottlenecks and Adjustment Costs - Isard, Peter; Aizenman, Joshua (Washington, D.C. : International Monetary Fund, 1993)
The paper discusses the case against a laissez faire approach to resource allocation and develops a model of supply bottlenecks. It argues that: (1) once budget constraints are hardened and credit markets begin to function appropriately, externalities associated with production bottlenecks and adjustment costs--other considerations aside--provide a case for subsidizing the costs of critical inputs for the state sector but not the new private sector; (2) the optimal subsidy declines as the private sector grows; and (3) the subsidy should be 'financed' by taxing wage income in the state sector, which will strengthen incentives for workers to move.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet